PJMHS 2022
DOI: 10.53350/pjmhs22163649
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health Insurance Project; Women Satisfaction Regarding Quality of Ante-natal Services

Abstract: Objective: This study aimed to evaluate the effectiveness of the universal health insurance project regarding the quality of health care with antenatal care services. Materials and methods: A descriptive comparative study carried out at ten Primary Health Care (PCH) centers affiliated to Port-said and Damietta governorates. Multi-stage sampling probability technique used for selecting these centers, simple random sample of 460 women chosen. Data was collected through two tools; women's satisfaction questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Moreover, a recent study compared the satisfaction of pregnant females attending family health centres affiliated with the universal health insurance system and those working under the umbrella of traditional insurance in egypt, and it was found that 69.1% of women were unsatisfied with the antenatal care services and available resources provided by traditional insurance. on the other hand, 79.1% of women receiving universal health insurance were satisfied with the services provided [19]. the consistency in results can be explained, as both studies were conducted in the same setting (Port Said, egypt) under the umbrella of the universal health insurance system.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, a recent study compared the satisfaction of pregnant females attending family health centres affiliated with the universal health insurance system and those working under the umbrella of traditional insurance in egypt, and it was found that 69.1% of women were unsatisfied with the antenatal care services and available resources provided by traditional insurance. on the other hand, 79.1% of women receiving universal health insurance were satisfied with the services provided [19]. the consistency in results can be explained, as both studies were conducted in the same setting (Port Said, egypt) under the umbrella of the universal health insurance system.…”
Section: Discussionmentioning
confidence: 79%